Poetry of the universe - Osserman, Robert (New York : Anchor Books, 1996)
A history of developments in mathematics from the geometry of the ancient Greeks to the twentieth-century concept of fractional dimensions, focusing on how these ideas have influenced theories in physics and expanded our understanding of the structure of the universe.
"A mathematical exploration of the cosmos"--Cover.
Includes bibliographical references (p. [174]-200) and index.
Library Journal Starred.
Wilson's Public Library.
Wilson's Senior High School.
Adult
Keywords: Mathematical physics -- Popular works; Mathematics -- Popular works; Mathematics; Physics -- Mathematics